2018
DOI: 10.1177/1354856517736979
|View full text |Cite
|
Sign up to set email alerts
|

YouTube channels, uploads and views

Abstract: To this date, it is difficult to find high-level statistics on YouTube that paint a fair picture of the platform in its entirety. This study attempts to provide an overall characterization of YouTube, based on a random sample of channel and video data, by showing how video provision and consumption evolved over the course of the past 10 years. It demonstrates stark contrasts between video genres in terms of channels, uploads and views, and that a vast majority of on average 85% of all views goes to a small min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(67 citation statements)
references
References 19 publications
1
43
0
5
Order By: Relevance
“…In practice it means a bet to limit the investment to the most attractive content. This action is consistent with user demand: 85% of the viewings are concentrated in 3% of the channels, which leads to the phenomenon rich-get-richer (Bärtl, 2018).…”
Section: In Search Of Profit: Youtube and Its Business Modelssupporting
confidence: 74%
“…In practice it means a bet to limit the investment to the most attractive content. This action is consistent with user demand: 85% of the viewings are concentrated in 3% of the channels, which leads to the phenomenon rich-get-richer (Bärtl, 2018).…”
Section: In Search Of Profit: Youtube and Its Business Modelssupporting
confidence: 74%
“…The "rich get richer effect" is common in social network platforms, and had already been identified and discussed in other works (Napoli, 2018). Concerning YouTube, Bärtl (2018) observed that a small number of channels (3% of them) concentrate around 85% of the video views on the entire platform. He attributed this phenomenon to two processes: first, videos and channels that already have more views have a greater sharing base; and second, there is a mismatch in the demand and supply of YouTube genres: there are too many channels belonging to low-demand genres (like People and Blogs) and too few channels that interest a broader audience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tanto es así que se les llega a calificar como la generación mute (Telefónica, 2019), caracterizada por hablar poco y utilizar como canal principal de comunicación las herramientas de mensajería instantánea. Una de las actividades más comunes realizadas por la gente joven en Internet es la monitorización de redes sociales (Gray, 2018;Bärtl, 2018), estando ya consideradas desde 2012 como el medio de información preferente para este grupo de personas (Devine y Lloyd, 2012; Catalina, García y Montes, 2015; García-Jiménez, Tur-Viñes y Pastor-Ruiz, 2018).…”
Section: Uso Del Teléfono Móvil Consumo De Información Y Jóvenesunclassified